PENANGANAN NON FARMAKOLOGI DENGAN KONSUMSI BAYAM UNTUK MENINGKATKAN KADAR HEMOGLOBIN PADA IBU HAMIL ANEMIA - Astri Yunifitri; Devy Lestari Nurul Aulia; Nova Roza (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2022)
Anemia often occurs due to iron deficiency because in pregnant women there is a twofold increase in iron requirements due to an increase in blood volume without plasma volume expansion, to meet the needs of the mother. One alternative to meet iron needs can be done by consuming vegetables that contain iron in the diet. Green spinach is a source of food that depends on compounds needed in the synthesis of hemoglobin such as iron and vitamin B Complex. The purpose of this literature review is to find out non-pharmacological treatments with consumption of spinach in anemic pregnant women, the method used is by browsing articles using electronic media with keyword guidance. From the search results, it was found that consumption of spinach can increase hemoglobin levels so that it can be used as a non-pharmacological treatment for pregnant women with anemia. Suggestions for pregnant women who experience anemia, can consume spinach as an alternative to increase hemoglobin levels and consume foods with balanced nutrition to meet the needs during pregnancy